A Decade of Implementation and Integration of Technology in Curriculum Management in Modern Pesantren - Syaharuddin Syaharuddin; Yudin Citriadin; Hazat Usman Mashwani (Alpatih Harapan Semesta, 2026)
This research is important to do considering the rapid development of technology that requires educational institutions, including modern pesantren, to adapt in improving the quality of curriculum management and learning quality. In addition, the need for leadership strategies that are responsive to technological change is also a crucial aspect in encouraging teacher professionalism. This study aims to examine the implementation and integration of technology in curriculum management in modern pesantren over the past decade. The approach used is qualitative research with the Systematic Literature Review (SLR) method. Data sources were obtained from two main databases, namely Dimensions and Scopus, with a publication range of the last ten years to ensure the relevance and novelty of the data analyzed. The main focus of this study is on leadership strategies in encouraging teacher professionalism through the use of technology in curriculum management. The findings further indicate that effective technology integration requires strategic leadership, continuous teacher professional development, and adequate digital infrastructure to ensure sustainable curriculum transformation in modern pesantren. This study contributes to the development of a conceptual understanding of technology-based curriculum management by synthesizing leadership, curriculum innovation, and digital transformation into an integrated perspective. The study recommends that policymakers and pesantren leaders formulate comprehensive digital curriculum policies accompanied by systematic teacher capacity-building programs to support sustainable educational quality improvement.